Instrumental temperature-dependence of backscatter measurements by a multibeam echosounder: findings and implications - Roche, Marc; Lønmo, Tor Inge Birkenes; Fezzani, Ridha; Berger, Laurent; Deleu, Samuel; Bisquay, Hervé; Gaillot, Arnaud; Vanparys, Kris; Vercaemst, Jan; Degrendele, Koen; Barette, Florian; Fonseca, Luciano Emidio; et al. (Frontiers in Remote Sensing, 2025)
Multibeam echosounder Backscatter Strength (BS) measurement is a pivotal tool for seabed mapping and monitoring. However, its effective utilization is contingent upon the resolution of challenges such as environmental influences, calibration and repeatability. Natural reference areas offer a pragmatic solution by providing a reliable foundation for backscatter quality control and calibration, ensuring data consistency over time. Recent measurements conducted on the Kwinte reference area (Belgian part of the North Sea) have revealed a significant correlation between measured BS and seawater temperature. This correlation is corroborated by other measurements carried out on the Carré Renard reference area (Bay of Brest, France) and in-tank (by Kongsberg Discovery, Horten, Norway). Significant measured level shifts were currently observed (up to 4 dB per 10°C), depending on signal frequency and angle, and described either as global level shifts or as directivity pattern distortions. Given the negligible impact of sound absorption through the water column, the level-temperature dependence assessed here is regarded as a sensor artifact. This finding underscores a heretofore unrecognized source of MBES-measured level variability. This instrumental temperature-dependence is attributable to variations in the properties of the materials constituting transducers and in their acoustic interaction, which, in turn, affect the sensitivity and directivity of the arrays and influence measured levels. A simple sound-speed-dependent description of in-transducer refraction offers an explanation for these effects but does not fully account for the observed changes in directivity patterns. Hence, it is necessary to consider complex models accounting for material interactions, transducer properties and coupling, and individual calibration. However, these models are challenging to build and implement comprehensively. A systematic cross-calibration during each measurement campaign is considered as a means to account for this variability. This pragmatic approach is demonstrated through its application to a short time series dataset, showcasing its benefits. This research advances key priorities in the concerned scientific community by enhancing the accuracy and reliability of BS as a seabed sediment indicator and refining cross-calibration over natural reference areas. It also advocates for the systematic use of backscatter measurements in marine resource management and habitat monitoring.